2022
DOI: 10.3390/su142114172
|View full text |Cite
|
Sign up to set email alerts
|

Whey as a Carrier Material for Blueberry Bioactive Components: Incorporation in White Chocolate

Abstract: White chocolate is considered an unhealthier product than dark and milk chocolate due to the absence of cocoa solids containing polyphenols and other valuable components such as minerals and dietary fiber. This paper aimed to improve the nutritional value of white chocolate (C) by adding blueberry bioactive compounds. Since natural polyphenols are easily degradable because of their sensitivity, whey, as a rich source of proteins, was used as a material for encapsulating blueberry juice. Whey proteins protect b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…In the six cottonseed butter products, the oxidation stability steadily was gradually reduced from 250 min with 36% oil to 65 min with 57% oil, indicating the oil ingredient was the key component of rancidity of these butter products. Using the same type of measurements, Jovanović et al [58] reported oxidation stability of white chocolate products with an oxidation induction time as long as 680 min due to increasing polyphenol contents. To calculate the shelf life per the oxidation stability, we further measured the oxidation induction time of B50 at 100, 120, and 140 • C. A linear equation ln(t[min]) = 8400.00 K/T-17.00 was drawn per the produced data.…”
Section: Oxidation Stability (Rancidity)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the six cottonseed butter products, the oxidation stability steadily was gradually reduced from 250 min with 36% oil to 65 min with 57% oil, indicating the oil ingredient was the key component of rancidity of these butter products. Using the same type of measurements, Jovanović et al [58] reported oxidation stability of white chocolate products with an oxidation induction time as long as 680 min due to increasing polyphenol contents. To calculate the shelf life per the oxidation stability, we further measured the oxidation induction time of B50 at 100, 120, and 140 • C. A linear equation ln(t[min]) = 8400.00 K/T-17.00 was drawn per the produced data.…”
Section: Oxidation Stability (Rancidity)mentioning
confidence: 99%
“…The oxidation stability was measured by an Anton Paar RapidOxy 100 m. The meter accelerates the oxidation process by using increased temperature and oxygen pressure [57,58]. The induction period, which is the total time between the heating of the test chamber until the 10% pressure drop, can be used as a measure of the oxidative stability of the sample (Figure 5).…”
Section: Oxidation Stability (Rancidity)mentioning
confidence: 99%
“…As opposed to the control group (iron overload), rats fed a whey protein diet showed greater blood levels of glutathione. This revealed that whey proteins may be able to change the DNA damage caused by elevated iron levels and lessen ROS in cells [ 60 ]. Pseudomonas aeruginosa is one of the recognized microorganisms that cause pulmonary infection and lung colonization, which lead to breathing problems [ 61 ].…”
Section: Applications Of Whey and Its Bioactive Components In Various...mentioning
confidence: 99%
“…In opposition to our previous study (Jovanović et al, 2022), which regarded to encapsulation of blueberry juice on whey as a carrier and its possible use as a functional ingredient in chocolates, this study deals with the encapsulation of blueberry juice on maltodextrin as a carrier and its impact on physical, chemical and sensory properties of white chocolate including its potential use as a functional ingredient.…”
Section: Introductionmentioning
confidence: 98%
“…As mentioned before, white chocolate does not contain dark cocoa solid particles, which are carriers of high amounts of phenolic compounds, making this product suitable for the enrichment and production of white chocolate with higher nutritional value. At this moment, there are some functional chocolates on the market that are enriched with cinnamon particles (Muhammad, Saputro, Rottiers, Van de Walle & Dewettinck, 2018), whey protein (Jovanović et al, 2022), probiotics (Hossain, Ranadheera, Fang & Ajlouni, 2020), green tea O N L I N E F I R S T extract (Lončarević et al, 2019), etc. In our previous research (Lončarević et al, 2018;Lončarević et al, 2019), green tea extract and blackberry juice were encapsulated using maltodextrin as a carrier and added to white chocolate.…”
Section: Introductionmentioning
confidence: 99%